QUALITY OF PHARMACOLOGICAL CORRECTION OF MODIFIED CARDIOVASCULAR RISK FACTORS AND TREATMENT OF CARDIOVASCULAR DISEASES IN PATIENTS WITH NON-INSULIN DEPENDENT DIABETES MELLITUS IN ENDOCRINOLOGY CENTERS - D. M. Urusbiyeva; S. R. Gilarevsky; L. V. Daurbekova (Российский кардиологический журнал)
Quality of pharmacological correction of modified cardiovascular risk factors and treatment of cardiovascular diseases in patients with non-insulin dependent diabetes mellitus in endocrinology centers.